Unconscious bias in property management organisations (PMOs): identifying bias trends and mitigation strategies - Zainol, Nurul Nadiah; Isa, Mona; Sukereman, Anis Syazwani; Sulaiman, Muhammad Azwan; Abdullah Hashim, Hariati (Universiti Teknologi MARA, Perlis, 2025)
This study investigates unconscious bias in Property Management Organisations (PMOs) in Selangor, focusing on its presence in recruitment, tenant selection, vendor engagement, and service delivery. The research aims to identify common bias types and evaluate effective mitigation strategies. Using convenience sampling, data were gathered through questionnaires from 70 PMO personnels, including managers, executives, and administrative staff. Descriptive analysis and the Relative Importance Index (RII) were used to rank prevalent biases and assess the perceived importance of mitigation strategies. Centrality Bias and Availability Bias emerged as the most common, especially in recruitment and tenant selection. Fostering an inclusive workplace culture and updating recruitment criteria were identified as the most effective mitigation strategies. Although limited to a single region, the study offers practical insights for promoting fairer and more inclusive decision-making in PMOs.